The Influence of Big Five Personality Traits on Online Purchase Intention Among University Students Using Lazada and Shopee - Siti Nur ’Aqilah Nazari; Siti Nur Dini Mohamad Shahrim; Siti Nur Inasya Muhe; Siti Nurhidayah Rosle; Aditya Aditya; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Today, university students are particularly dependent on online shopping, especially on popular e-commerce sites such as Lazada and Shopee. The purpose of this study is to explore more the relationship between the Big Five Personality Traits and online purchase intentions among university students who are habitual consumers on this platform. A quantitative research design will be adopted and a sequence of variables will be collected via online questionnaire that will be sent through Google Form. The Big Five Inventory (BFI-44) will be used to measure the personality traits while the online purchase intentions item will be modified fromPavlou (2003) and Ha Stoel (2009). The target sample for the study will be 150 university students across Malaysia. Data will be collected and will be analysed through descriptive and correlation analysis to illustrate the relationship between the variables. It is expected that openness to experience, consciousness and extraversion will positively influence online purchase intentions, agreeableness will have a moderate influence and neuroticism will have a negative influence. Ultimately, the findings to aim the contribute knowledge to e-commerce platform for developing personality focused marketing methods and enhancing personalization in online shopping experiences.